Physical hydrogel with tunable flowability and self-recovery properties through introducing branched polymer and nanoparticle. (3rd June 2020) - Wang, Li; Guan, Yinyan; Ming, Hao; Gao, Weichun; Shen, Xinjun; Wang, Xiaolei; Liang, Jiyan
Abstract: To achieve injectability and printability of hydrogels, physical hydrogels with tunable flowability and self-recovery properties are reported in this article. Flowability of polyacrylamide (PAAm) physical hydrogel is adjusted by introducing branched polyethyleneimine (PEI) with a large number of –NH2 and –NH– groups. The AAm5 physical gel, which is generally solid-like and elastic (G' > G″), can transform to a shear-thinning and viscous fluid after introducing a certain amount of PEI. But following that transformation, its strength decreased. The strength of PEI/PAAm hydrogels can be improved by SiO2 nanoparticle. The G′ of PEI/PAAm/SiO2 physical gels increased with SiO2 mass concentration increasing, indicating that the strength and viscoelastic behavior of PEI/PAAm/SiO2 physical gels were dependent on SiO2 mass concentration. Moreover, the self-recovery property of PEI/PAAm/SiO2 physical gels was studied by three cycles of alternating strain and time sweeps. The results showed that AAm5 -PEI0.02 -TM500.08 and AAm5 -PEI0.02 -SM0.08 gels display a remarkable self-recovery property after three cycles of alternating strain sweep and time sweep. And strain thinning behavior of AAm5 -PEI0.02 -TM500.08 gel was observed at larger strain amplitude.